Non-Linear Regression Models to Predict the Lamb and Sheep Weight Growth - Ullah, Muhammad Aman; Amin, Muhammad; Abbas, Muhammad Ansar (Pakistan Journal of Nutrition, 2013)
The study of living organism growth is the hot issue now a days in biological sciences. In this research, we explore the descriptive analysis of Lamb and Sheep weight growth in Pakistan. Also the non-linear regression models are identified on the basis of model selection criteria’s for lamb and sheep weight growth prediction. From the analysis, we have found that for commercial sheep, spring born lambs and twin born lambs, the best model is the Von Bertalanffy model. While for predicting the weight of male commercial sheep, autumn born and single born lambs, the best model is the Brody model.